Understanding the Role of Gibberellic Acid and Paclobutrazol in Terminal Heat Stress Tolerance in Wheat - Nagar, Shivani; Singh, V. P.; Arora, Ajay; Dhakar, Rajkumar; Singh, Neera; Singh, G. P.; Meena, Shashi; Kumar, Sudhir; Shiv Ramakrishnan, R. (Frontiers in Plant Science, 2021)
Understanding physiological mechanism of tolerance is an imperative for crop improvement under stresses. The role of plant hormones is well established in abiotic stress tolerance. However, the information on role of gibberellic acid (GA) in abiotic stress tolerance in late sown wheat is insufficient in literature. Thus, we aimed to investigate the role of endogenous GA3 level in stress tolerance in contrasting wheat cultivars viz., temperature tolerant (HD 2643 and DBW 14) and susceptible (HD 2189 and HD 2833) under timely and late sown condition. The variation in endogenous GA3 level was created by exogenous spray of GA3 and its biosynthesis inhibitor paclobutrazol (PBZ). Tolerant genotypes maintained higher antioxidant enzymes activity, membrane stability, photosynthesis rate, lower lipid peroxidase activity, H2O2 content attributing to better growth and yield traits under late sown conditions. Paclobutrazol escalated antioxidant enzymes activity, photosynthesis rate and reduced the lipid peroxidation and ion leakage in stress thus improved thermo-tolerance. GA3 had non-significant effect on antioxidant enzyme activity, lipid peroxidation and membrane stability while increased the test weight in most of the cases. GA3 upregulated GA biosynthesis and degradation pathway genes and PBZ down regulated kurene oxidase and GA2ox gene expression. GA3 upregulated cell expansins gene expression under both environmental conditions. Exogenous GA3 did not increase thermo-tolerance but had positive effect on test weight and cell expansins gene expression. We found no direct relationship between endogenous GA3 content and stress tolerance traits, which indicates that PBZ could have conferred thermotolerance through alternative mechanism instead of inhibition of GA3 biosynthesis